Developing Edutainment-Based Comic Media in Integrative-Thematic Learning in the Elementary School - Rani Febriyanti; Ali Mustadi (UIN Siber Syekh Nurjati Cirebon, 2020)
AbstractThe aim of this research is to develop edutainment-based comic media in thematic-integrative learning in fifth grade of elementary school. This study is a Research and Development (R&D) using the Borg and Gall model. The data were obtained through observation, interviews, and questionnaires. The results of comic media were obtained through a media expert product evaluation questionnaire and material from experts, educational practitioners, and peers. While the trial results were obtained through a questionnaire response given to 72 fifth grade elementary school students. The results of the validators indicate that the comic media is very feasible to be seen from the aspect of the media with an average is 92,27%, it is also considered very feasible from the aspect of the material with an average is 91,63%. Validation results with education practitioners get an average of 81,5% and 87,82% for peers with the criteria very good. The results of small class trial get an average is 84,72% and large class trial get an average of 91,6% with very good criteria. It also obtained an average is 91,6% from the teachersâ€™ response questionnaire with criteria very good. Based on the results, the edutainment-based comic media is very feasible for SD/MI teacher to be used in integrative thematic learning. Most students believed that comics contribute to facilitate understanding of the concept of the material and provide fun for students in reading.Keywords: comic media, edutainment, integrative-thematic learning.Â Â AbstrakPenelitian ini bertujuan untuk mengembangkan media komik berbasis edutainment dalam pembelajaran tematik-integratif di kelas V Sekolah Dasar. Penelitian ini merupakan penelitian pengembangan dengan menggunakan model Borg and Gall. Data penelitian ini diperoleh melalui observasi, wawancara, dan angket. Hasil kelayakan media komik berbasis edutainment diperoleh melalui angket penilaian produk ahli media dan ahli materi, guru kelas, dan teman sejawat. Sedangkan hasil uji coba diperoleh melalui angket respon yang diberikan kepada 72 siswa kelas V SD. Hasil validasi ahli menunjukkan bahwa media komik berbasis edutainment sangat layak dilihat dari aspek media dengan rata-rata 92,27% dan aspek materi dengan rata-rata 91,63%. Hasil validasi oleh praktisi pendidikan mendapatkan rata-rata 81,5% dan penilaian teman sejawat mendapatkan rata-rata 87,82% dengan kriteria sangat baik. Hasil uji coba kelas kecil mendapatkan rata-rata 84,72% dan uji coba kelas besar memperoleh rata-rata 91,6% dengan kriteria sangat baik. Guru juga merespon sangat baik terhadap media komik berbasis edutainment dengan memperoleh rata-rata 91.6%. Sehingga dapat disimpulkan bahwa media komik berbasis edutainment sangat layak digunakan dalam pembelajaran tematik-integratif di sekolah dasar. Banyak siswa yang meyakini bahwa komik mampu memfasilitasi pemahaman konsep materi dan memberikan kesenangan dalam membaca.Kata kunci: media komik, edutainment, pembelajaran tematik-integratif.